Uma visão sobre a eco-epidemiologia da hantavirose: revisão sistemática e fatores socioambientais associados - Furtado, Michelle Andrade (2011)
The unstructured urbanization, social exclusion and with major engineering projects such as dams, roads, and expanding agricultural frontiers that occupy natural areas not previously inhabited, are some of the consequences of population growth that generate well-known situations in everyday life of everyone. These actions have caused irreversible loss of biodiversity and ecosystem services and have a direct impact on human health. Environmental degradation is reported as a common condition among the features related to the occurrence of emerging diseases, but is seldom considered in policy strategies, in which treatment is the rule before the disease prevention and health promotion. The actual discussions which include new production strategies, integration of knowledge and intervention from the possibility of interdisciplinary action. Thus, this study was to determine the consequences of environmental change on human health. For this purpose, this study was divided into two stages. The first was on the systematic review of the Hantavírus. This showed that few studies address the relationship of environment to outbreaks of Hantavírus compared with molecular studies on the virus. The second part of this study aims to identify the social and environmental aspects of areas of transmission of Hantavírus in Brazil. The results showed that deforestation resulting from the expansion of farming has reduced large tracts of forests into small fragments and the fragmentation favors generalist species, like those of wild rodents are reservoirs of Hantavírus and these environmental changes contribute to outbreaks of diseases such as Hantavírus, in human populations, because they promote a closer relationship between humans and rodents. Are necessary increase of conservation areas in order to maintain a stable ecosystem with predators for population control of rodents and campaigns on the modes of transmission, infection and good storage practices of agricultural production in order to avoid proliferation of rodents, especially for vulnerable populations.